Analisis Pengaruh Kekuatan Otoritas Pajak terhadap Kepatuhan Wajib Pajak dengan Moral Pajak sebagai Variabel Mediasi pada UMKM di Jakarta Pusat - Sabina Berlina Gulo; Ratnaningrum Ratnaningrum; Sri Wahyuning; Eni Endaryati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
This study focuses on micro, small, and medium enterprises (MSMEs) in Central Jakarta, which play an important role in the national economy, particularly through their contribution to state revenue from the taxation sector. The purpose of this study is to examine how taxpayers’ knowledge and compliance with tax regulations influence tax revenue generated from the MSME sector. The distribution of questionnaires to MSME taxpayers was used as the main instrument to collect research data through a quantitative approach. A total of 164 respondents were selected using a purposive sampling method by considering specific criteria relevant to the research objectives. To evaluate and analyze the collected data, this study employed SmartPLS software using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that tax revenue from MSMEs is positively and significantly influenced by taxpayer compliance in fulfilling their tax obligations. Furthermore, there is a positive and statistically significant relationship between the level of tax knowledge and the increase in tax revenue. These findings highlight the importance of improving taxpayers’ understanding and compliance as an effort to enhance tax revenue from the MSME sector. This study is expected to provide practical contributions to the Directorate General of Taxes in formulating more effective policies to improve compliance and optimize tax revenue from MSME taxpayers.